2021
DOI: 10.1186/s43055-021-00549-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Egypt after a year: the first and second pandemic waves from the radiological point of view; multi-center comparative study on 2000 patients

Abstract: Background One year has passed since the announcement of COVID-19 as a pandemic and two waves had already stricken Egypt. The authors witnessed several atypical radiological features through the second pandemic wave, either early at the active infective stage or delayed at the post-infectious convalescent period. They believed every radiologist should be familiar with these features. Therefore, they performed this comparative study on 2000 Egyptian patients using multi-slice computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…We found two studies that compared CT findings of different patients between the first and second pandemic waves, one done in Ghana [ 31 ] and the other in Egypt [ 18 ]. In our study, we compared CT findings in the same patients that infected twice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found two studies that compared CT findings of different patients between the first and second pandemic waves, one done in Ghana [ 31 ] and the other in Egypt [ 18 ]. In our study, we compared CT findings in the same patients that infected twice.…”
Section: Discussionmentioning
confidence: 99%
“…In the study done in Egypt [ 18 ], they reported some atypical CT findings which were only encountered during the second pandemic wave. They included the bronchiectatic changes, the “head-cheese” pattern, the “bulls-eye” sign and the cavitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations